2008
DOI: 10.1002/adfm.200700673
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly of Organic/Inorganic Building Molecules with ππ Interactions

Abstract: Hierarchical assemblies of perylenetetracarboxylic diimide bridged silsesquioxane (PDBS) with controlled structure at multi‐length scale are studied using both experimental and computational methods. The organization process spans multi‐length scales and includes three continuous steps: 1) stacking of the preprogrammed molecules into small clusters, 2) growing of the small clusters into nanoscale building blocks with various sizes and shapes depending on the experimental conditions, and 3) aggregation of nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 70 publications
(42 reference statements)
2
24
0
Order By: Relevance
“…[12] However, it is generally known that chromophore aggregation can quench light emission due to increased excited state relaxation through nonradiative pathways. [13] Thus, the synthesis of fluorophores with strong emissions in the aggregate states through 1D self-assembly is intriguing, although such materials are seldom reported. Recently, Park prepared several organogels by the self-assembly of low-molecular-weight fluorophores and found that the emission is induced or enhanced along the stacking direction.…”
Section: Introductionmentioning
confidence: 99%
“…[12] However, it is generally known that chromophore aggregation can quench light emission due to increased excited state relaxation through nonradiative pathways. [13] Thus, the synthesis of fluorophores with strong emissions in the aggregate states through 1D self-assembly is intriguing, although such materials are seldom reported. Recently, Park prepared several organogels by the self-assembly of low-molecular-weight fluorophores and found that the emission is induced or enhanced along the stacking direction.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Although the electrostatic interaction is often used to drive the multilayer assembly, other driving forces including covalent bonding, hydrogen bonding, and hydrophobic interactions have been also exploited in the past decade. [5][6][7][8][9][10][11] This facilitates the incorporation of a broad range of functionality into capsules and planar surface using LbL assembly strategy, thereby increasing the potential application spectrum of the asprepared materials. [5,10,[12][13][14][15][16][17][18] Recently, organic-inorganic hybrid multilayers synthesized by LbL assembly have fascinated many researchers due to their delicate structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Organosilanes are ideal candidates for such efforts due to their ability to self-assemble and the intrinsic hybrid configuration of organic/inorganic moieties. Yet, the main emphasis has been focused on alkylsilane, where an alkyl group is linked with a silane terminal, i.e., R-SiX 3 (R is alkane and X can be halogen or alkoxy).…”
mentioning
confidence: 99%